Evaluation of Anti-fungal Properties of Pawpaw and Tamarind Leaf Extracts against Fusarium Head Blight in Both Wheat and Millet - Nnebechukwu, Ijeoma Adaku; Garba, Finji Kokshak; Obidigbo, Chidiebere Benjamin (Direct Research Journal of Biology and Biotechnology, 2024)
This research on the production of antifungalwas focused on the prevention of Fusarium head blight (FHB) associated with the head wilt in both wheat and Millet, and the isolation and identification of fungi associated with Fusarium head blight in both Wheat and millet. Fusarium-damaged kernels (FDK) which are characterized as shrivelled, light, and dull greyish or pinkishof both wheat and millet., packaged in a clean polythene and transported the laboratory to preparation.500gms of the samples was disinfected in 70% ethanol for 1minute and then transferred to 10% sodium hypochlorite solution and allowed for 30mins before it was rinsed in three (3) changes of distilled water and air dried on foil paper. The samples solutions were transferred to potatoes dextrose agar (PDA) plates already prepared and we're incubated at 25°-37°C for 5days.The research work was able to confirm that Fusarium graminearum and Fusarium ventricosum are the major causes of Fusarium head blight in wheat and millet. However, secondary contaminants such as Aspergilusniger, Aspergilus flavus and Rhizopus were also present. The data collected in terms of occurrence of fungal isolates and mycelial growth per concentration of extracts for tamarind and pawpaw leaf were tabulated and analyzed using Chi-square and ANOVA using Duncan Post hoc in SPSS version 26. A p-value
Keywords: phytochemical; extract, fungi; analysis